Cardiac fibroblasts in heart failure and regeneration - Harrington, Alenca; Moore-Morris, Thomas (Frontiers in Cell and Developmental Biology, 2024)
In heart disease patients, myocyte loss or malfunction invariably leads to fibrosis, involving the activation and accumulation of cardiac fibroblasts that deposit large amounts of extracellular matrix. Apart from the vital replacement fibrosis that follows myocardial infarction, ensuring structural integrity of the heart, cardiac fibrosis is largely considered to be maladaptive. Much work has focused on signaling pathways driving the fibrotic response, including TGF-β signaling and biomechanical strain. However, currently there are very limited options for reducing cardiac fibrosis, with most patients suffering from chronic fibrosis. The adult heart has very limited regenerative capacity. However, cardiac regeneration has been reported in humans perinatally, and reproduced experimentally in neonatal mice. Furthermore, model organisms such as the zebrafish are able to fully regenerate their hearts following massive cardiac damage into adulthood. Increasing evidence points to a transient immuno-fibrotic response as being key for cardiac regeneration to occur. The mechanisms at play in this context are changing our views on fibrosis, and could be leveraged to promote beneficial remodeling in heart failure patients. This review summarizes our current knowledge of fibroblast properties associated with the healthy, failing or regenerating heart. Furthermore, we explore how cardiac fibroblast activity could be targeted to assist future therapeutic approaches.